Chronic low back pain and walking speed: effects on the spatiotemporal parameters and in gait variability - Carvalho,Alberito Rodrigo (2019)
ABSTRACT BACKGROUND AND OBJECTIVES: Walking is described as one of the abilities most affected by chronic low back pain. This study aimed to determine if chronic nonspecific low back pain and walking speed affect the spatiotemporal parameters (stride length, swing time, contact time, stride time, stride frequency and walking ratio) and the coefficients of variation of stride length and contact time. METHODS: Ten participants with chronic nonspecific low back pain (low back pain - LG) and ten healthy participants in the control group (CG) walked on the treadmill at preferred self-selected speed, slower and faster than the preferred speed. Spatiotemporal parameters and coefficients of variation were determined by kinematic analysis. Main effects (group and speed) and their interactions were tested using generalized estimating equations method. RESULTS: Our results showed that there were no significant differences between groups or significant interaction between group and speed factors. There was a speed effect. Stride frequency and length increased while contact and stride time decreased as the speed increased. The walking ratio (stride length/stride frequency) was relatively consistent across speeds (~1.6 m·stride-1.s) without statistical differences. The coefficients of variation were below 5%. CONCLUSION: The chronic nonspecific low back pain did not affect the gait spatiotemporal profile, at least for those patients classified as chronic nonspecific low back pain according to the signs and symptoms criteria. Although the preferred speed has affected the spatiotemporal parameters, both groups patients were able to adjust their kinematic parameters to each task demand.